The Tombs of the Righteous and Cosmic Energy in Ukraine - Zatorska, Magdalena (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2023)
Drawing on ethnographic fieldwork in the town of Uman (Ukraine), an important Hasidic pilgrimage centre built around the tomb of the Jewish righteous rabbi Nachman of Bratslav, I explore the notion of energy employed by Uman’s non-Hasidic and non-Jewish inhabitants to describe the pilgrimages and their impact on the town. I argue that for some of the Uman residents energy, as a part of a wider set of ontological convictions, explains the agency of human and other-than-human actors, as well as the animacy of the world they inhabit. In this contribution, I show how the notion of energy reflects the local and supralocal contexts, in particular the struggles for national identity and sovereignty and is employed in the process of co-creating the Hasidic pilgrimage to Uman by the pilgrimage’s “others”.
24 cm
Keywords: pilgrimage; Hasidism; agency; Energy; Ukraine